Peningkatan Hasil Belajar Siswa melalui Keterampilan Proyek - Suyono Suyono (Syntax Corporation Indonesia, 2024)
The objectives of this study are: (1) Knowing the achievement of student skills learning outcomes after learning using the Project Skills method. This research is an action research (action research), because the research is carried out to solve learning problems in the classroom. This research also includes descriptive research, because it describes how a learning method is applied and how the desired results can be achieved. Based on the findings of the research above, it can be concluded that the application of the Project Task model on local handicraft product material in class XII MIPA 2 SMA Negeri 2 Madiun is effective in improving process skills in working on project tasks in PKWU subjects.